Spiders and mushrooms: Reporting bowel endometriosis shape on preoperative MRI to flag surgical complexity. Issue 7 (2nd February 2022) - Youn, Paul; Copson, Sean; Jacques, Angela; Haliczenko, Kylie; McDonnell, Rose; Lo, Glen
Abstract: Introduction: Preoperative imaging of patients with endometriosis allows adequate counselling, referral to appropriate centres of expertise and workforce planning. The objective of this study was to assess the feasibility of simplified three‐category preoperative endometriosis MRI morphological descriptors to predict subsequent surgical management. Methods: A single‐centre observational study in 76 patients (median age 38 years, range 18–55) with preoperative endometriosis mapping MRI between 1 Jan 2015 and 31 Dec 2019. MRI studies were prospectively re‐read blind‐to‐surgical outcome to categorise rectosigmoid morphology as normal, spider‐shaped (linear T2‐dark fibrotic bands) superficial endometriosis or typical crescentic or mushroom‐shaped deep infiltrating endometriosis (DIE). Bowel motility was similarly categorised as normal, tethered or distorted/fixed. The reference standard was subsequent surgery within 3 years of MRI, categorised as no bowel surgery, adhesiolysis only or more complex surgeries. Results: Despite three‐quarters of surgical cases having normal bowel morphology on preoperative MRI (72%, 55/76; 12% linear superficial endometriosis, 10% crescentic and 5% mushroom‐shaped DIE) more than half showed bowel tethering (54%, 41/76) or distortion/fixation (10%, 8/76) and most patients underwent adhesiolysis (79%, 60/76). Complex surgery such as bowel resection, laparotomy conversion or complex adhesiolysis is predicted by morphology (crescentic or mushroom‐shaped DIE, P  < 0.001) and motility (tethered or distorted bowel, P  = 0.002) descriptors. Conclusions: Comprehensive and clinically relevant diagnostic reporting does not have to be convoluted to have clinical impact: in our study population, categorising bowel morphology as normal, spider‐shaped (superficial) or crescentic/mushroom‐(DIE) shaped and motility as normal, tethered (superficial) or distorted/fixed (deep endometriosis) correlates to subsequent surgical complexity.